Die Mallophagen von Sturmvögeln und Ruderfüßern. I. Harrisoniella Bedford und Perineus Thompson (Mallophaga). (Nachtrag). - Kéler, Stefan von (Contributions to Entomology = Beiträge zur Entomologie, 1958)
In the present supplement to the three continuations of the paper under the same title the material of Col. K. C. Emerson is treated. A new species, Perineus tenuipenalis n. sp. is described and supplementary remarks to four previously treated species ase made. Critical opinion to the question of the genotype of Harrisoniella is placed under the discussion of the genus Harrisioniella. Nomenclatural Acts tenuipenalis Kéler, 1958 (Perineus), spec. n.